The Economy of Open and Distance Learning: Evidence from Literature Review - Ngoboka, Mkanibwa; Ndawi, Joseph; Ndekwa, Alberto Gabriel (IJRDO- Journal of Educational Research, 2017)
This paper focused on analyzing the significant contribution of Open and Distance learning in inclusive growth education and its economy in general. Data collection was based on documentary review of 15 empirical studies in Africa and worldwide. Content analysis was used in analyzing data collected from prior empirical studies. Finding using content analysis has indicated that open and distance learning offer inclusive growth education to disadvantage population. In additional, financial saving, education services, poverty reduction, time saving and women empowerment where identified as an economy played by open and distance education. The study recommended that the Nation education scheme of any developing countries should be enforced and encouraged to facilitate open and distance system in order to boost social economic development and include the disadvantage population in higher education system.